Analisis Tingkat Pemahaman Siswa Terhadap Mata Pelajaran Matematika Menggunakan Algoritma C4.5 - Faby Apella Prayetno Putri; M. Yusuf Ramadhan Nasution (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Education is a fundamental aspect of human life that gives every individual in Indonesia the opportunity to develop optimally. Schools as formal institutions have an important role in educating students and shaping a learning environment that is relevant and beneficial for their future. Students' understanding of subjects, especially mathematics, is one of the main indicators of educational success. Given the abstract and multilevel nature of mathematics, many students at the school level experience difficulties in understanding this subject. Therefore, it is necessary to analyze the level of students' understanding of mathematics in order to improve the effectiveness of learning. This research aims to analyze the factors that influence students' level of understanding of mathematics subjects at Pematang Siantar State Junior High School 2 by applying data mining techniques using the C4.5 algorithm. This research also aims to measure the accuracy and performance of the C4.5 algorithm in classifying students' level of understanding, with data analyzed using the Python programming language through the Google Colab platform. The method used in this research involves applying the C4.5 algorithm to process and classify data. This algorithm enabled the researcher to identify learners' comprehension levels with a measured accuracy of 93.83%, indicating that the technique was effectively used in the analysis. Thus, the application of data mining using the C4.5 algorithm in SMP Negeri 2 Pematang Siantar can be an efficient tool in identifying obstacles in learning mathematics and potentially improving the quality of education in the school